Microservices with Azure : software architecture patterns to build enterprise-grade MicrNamit Tanasseri, oservices using Microsoft Azure Service Fabric /: software architecture patterns to build enterprise-grade MicrNamit Tanasseri, oservices using Microsoft Azure Service Fabric. (2017) - Tanasseri, Namit; Rai, Rahul
No abstract available